Grand Duke Nikolai Pavlovich as a Caricaturist: Who is “Ouf!” Depicted on the Caricature from the Winter Palace Library’s Collection of His Drawings - Vyskochko, Leonid V.; Shelaeva, Alla A. (Actual Problems of Theory and History of Art, 2018)
One of the most significant spheres of Emperor Nicholas I’s activity was his policy in the sphere of culture and art. It used to be traditionally characterized as an influence of the “unenlightened” absolutism. The characterization of Nicholas I as a person and his attitude to art can not be complete without the study of his drawings, which are kept in the archives, for the most part in the State Archive of the Russian Federation. They testify to his high level of professionalism as a graphic artist and cartoonist. The collection of Nicholas I’s drawings has recently become the subject of examination. Now the attribution of historical figures depicted by the crowned artist is one of important problems. Normally Nicholas I did not name the prototypes of his drawings. Sometimes they are intently encoded. Parallel study of writing (especially the “Notebooks” of the Grand Duke Nicholas) and visual sources enables us to make well-grounded conclusions. Thus, as M. V. Sidorova, M. N. Silaeva and A. A. Litvin determined, one of the cartoons with an original signature “Ouf” and another one “A Reserve Army Officer” (from the collection of drawings of the Winter Palace library) depicts the commander of the Guards Corps — General Fedor Petrovich Uvarov (1769-1824). The critical attitude of Nicholas I towards Uvarov was defined by his participation in a Palace coup d’etat March 11, 1801 and tensions in time when Nicholas Pavlovich was the commander of the brigade. The available iconography of General Uvarov gives additional material for the attribution of the drawing. Lifetime images of Uvarov (the portraits by Janosh Rombauer and George Dawe and the engraving by Francesco Vendramini) depicted General with his distinctive hairdo and recognizable curls as in Nicholas’ drawing. Analyzed material allows us to make more exact the number of satirical drawings, the time of their making and to conclude that Nicholas I was a talented painter who managed to express his attitude to nature and to rise to the abilities of artistic generalization in his satirical drawings.
Keywords: Nicholas I; cartoonist; pencil drawings; material for the attribution; F. P. Uvarov; Janos Rombauer; Francesco Vendramini